OVERWEIGHT/ OBESITY AMONG SCHOOL GOING ADOLESCENTS AND ITS ASSOCIATED FACTORS - A CROSS SECTIONAL STUDY IN AN URBAN LOCALITY OF EASTERN INDIA - LIPILEKHA PATNAIK; SUMITRA PATTANAIK; E VENKATA RAO; TRILOCHAN SAHU (International Journal of Pharma and Bio Sciences, 2015)
Overweight and obesity are an increasingly prevalent nutritional disorder among adolescents and its prevention is a public health priority. The study aims to know the prevalence of obesity among school going adolescents and to assess the associated factors. The present study was a cross sectional study conducted in 12 schools of Bhubaneswar from July 2013 to December 2013. 1800 adolescents of 10-16 years (Class VI to X) were included in the study. The overall prevalence of overweight and obesity among school going adolescents was found to be 27.8% (overweight-16.4% and obesity-11.4%). Overweight/ Obesity was significantly higher in adolescents with working mothers, joint family, having less than 2 siblings, not doing regular exercise, watching television more than 2 hours/day, playing computer games, consuming junk food regularly and not playing of outdoor games. There is a need for periodic screening for overweight in schools followed by counselling of parents of overweight adolescents.